2013
DOI: 10.2298/tsci120727004p
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of photovoltaic systems electricity generation using homer software in specific locations in Serbia

Abstract: In this paper basic information of Homer software for PV system electricity generation, NASA - Surface meteorology and solar energy database, RETScreen, PVGIS and HMIRS (Hydrometeorological Institute of Republic of Serbia) solar databases are given. The comparison of the monthly average values for daily solar radiation per square meter received by the horizontal surface taken from NASA, RETScreen, PVGIS and HMIRS solar databases for three locations in Serbia (Belgrade, Negotin and Zlatibor) is given. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…The daily electricity production as well as global irradiation for all the districts are recorded as maximum from March until October months and minimum during January, February, November and December. The results are in agreement with the studies carried out for different countries around the world [10,[21][22][23][24][25][26][27][28]. Figure 3 shows the mean monthly electricity generation (Em) as well as the monthly mean global irradiation per square meter (Hm) for the six districts of Khyber Pakhtunkhwa.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The daily electricity production as well as global irradiation for all the districts are recorded as maximum from March until October months and minimum during January, February, November and December. The results are in agreement with the studies carried out for different countries around the world [10,[21][22][23][24][25][26][27][28]. Figure 3 shows the mean monthly electricity generation (Em) as well as the monthly mean global irradiation per square meter (Hm) for the six districts of Khyber Pakhtunkhwa.…”
Section: Resultssupporting
confidence: 88%
“…Therefore it was concluded that PVGIS prediction is suitable for longer periods such as one year but not appropriate for single months [26]. More studies around the world discussed similar results [2,[9][10]20,[27][28][29]. Figure 4 depicts the estimated electricity production (kWh) per year from a PV system for the six districts of Khyber Pakhtunkhwa, Pakistan.…”
Section: Resultsmentioning
confidence: 96%
“…In the paper [27] were analyzed solar energy resources from different databases. The results show significant differences in the values of solar energy obtained using a different solar database.…”
Section: Solar and Wind Energy Potentialmentioning
confidence: 99%
“…The study reported that the unreliable grid consideration increased the cost of energy (COE) as compared to 24 h availability of the grid. Beside these, several studies are carried out for grid connected PV [23][24][25][26] and PV-wind-diesel hybrid power systems [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%